Efficacy of Hyaluronic Acid in Radiation Proctitis: A Case Series - Marcellus Simadibrata; Saskia Aziza Nursyirwan; Rabbinu Rangga Pribadi; Angelica Abigael; Lidya Tanjaya (Acta Medica Indonesiana)
Gastrointestinal toxicities of radiation might develop after exposure, thus leading to conditions such as abdominal pain, rectal bleeding, diarrhea, anemia, and weight loss. The development of drugs to reduce mucosal damage progression has been a focus on managing radiation proctitis. Radiation proctitis resulting from exposure to pelvic radiotherapies is effectively managed with topical administration on the anal mucosa. The clinical use of hyaluronic acid offers an innovative approach to managing radiation injury. Hyaluronic acid has multiple beneficial properties, such as regulating immune process to reduce inflammation and oxidative stress, supporting natural protective mechanism, promoting mucosa healing, and improving tissue hydration. Therefore, this case series introduces the idea that application of hyaluronic acid could potentially improve patients’ clinical conditions.